2019
DOI: 10.1177/0022034519865187
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Approach for Diagnosing TMJ Osteoarthritis

Abstract: This study’s objectives were to test correlations among groups of biomarkers that are associated with condylar morphology and to apply artificial intelligence to test shape analysis features in a neural network (NN) to stage condylar morphology in temporomandibular joint osteoarthritis (TMJOA). Seventeen TMJOA patients (39.9 ± 11.7 y) experiencing signs and symptoms of the disease for less than 10 y and 17 age- and sex-matched control subjects (39.4 ± 15.2 y) completed a questionnaire, had a temporomandibular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 34 publications
0
73
0
Order By: Relevance
“…A natural language processing–based model was successful in differentiating TMD-mimicking conditions from genuine TMDs, according to the frequency of word usage in the patient’s chief complaint and mouth-opening size (Nam et al 2018). ANNs based on CBCT revealed a 91.2% degree of conformity as compared with clinician consensus in classifying condylar morphology (Shoukri et al 2019). By integrating patients’ chief complaints, clinical and biochemical indicators, and objective radiomic features into training data sets and collecting larger samples of these data sets, a computer-assisted diagnosis system is warranted to improve TMD diagnostic accuracy.…”
Section: Applications Of Ai In Dentistrymentioning
confidence: 99%
“…A natural language processing–based model was successful in differentiating TMD-mimicking conditions from genuine TMDs, according to the frequency of word usage in the patient’s chief complaint and mouth-opening size (Nam et al 2018). ANNs based on CBCT revealed a 91.2% degree of conformity as compared with clinician consensus in classifying condylar morphology (Shoukri et al 2019). By integrating patients’ chief complaints, clinical and biochemical indicators, and objective radiomic features into training data sets and collecting larger samples of these data sets, a computer-assisted diagnosis system is warranted to improve TMD diagnostic accuracy.…”
Section: Applications Of Ai In Dentistrymentioning
confidence: 99%
“…Theoretically, the collective clinical data of TMDs examinations, if they can be translated into a well-structured and organized computer language, are able to differentiate between absolute TMDs diagnosis and other clinical conditions mimicking TMDs [ 65 ]. A study by Shoukri et al (2019) showed that the neural networks are able to program and classify the TMDs based on the combination of condylar radiographic imaging utilizing CBCT, biological markers such as saliva, and a variable range of clinical indicators including detailed facial and muscle pain and soreness history, range of mouth opening, and other signs such as headaches [ 66 ].…”
Section: Artificial Intelligence (Ai)mentioning
confidence: 99%
“…Histologically, abnormal synthesis and degradation of articular chondrocytes, extracellular matrix and subchondral bone are detected; as a result, the cartilage becomes thinner and stripped, and subchondral bone is exposed and scleroid [2]. The pathogenesis of TMJ-OA involves in ammation, excessive mechanical stress, abnormal remodeling of subchondral bone, chondrocyte apoptosis, catabolic disturbances and genetic factors, in which accelerated subchondral bone turnover plays a role in the initiation of TMJ-OA [3].…”
Section: Introductionmentioning
confidence: 99%